(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
The ethnomathematics approach views mathematics as an integral part of a community’s cultural practices. This study highlights the traditional cuisine of Apam Pinang, a specialty of Pontianak, as the object of study to identify the mathematical elements contained therein. The purpose of this study is to explore the mathematical concepts that arise in the process of making and serving Apam Pinang through qualitative methods with an ethnographic approach. Data collection was conducted through direct observation, interviews with Apam Pinang sellers, and documentation in the form of photographs. Data analysis was carried out following the stages proposed by Miles and Huberman, namely data reduction, data presentation, and conclusion drawing. The results of the study show that the process of making and serving traditional Apam Pinang cakes involves various mathematical concepts that are important and applicable in everyday life. Some of these include the cylindrical shape of the dough container, the circular and semicircular shapes of the molds, and the use of ratios and time measurements during the cooking process. This study contributes to the documentation of local culture while expanding the study of ethnomathematics based on traditional cuisine.